The Effect of Social Interaction on Learning Motivation of Students in Class X Accounting Expertise Program at SMKN 1 Makassar - Fitrianti Fitrianti; Sahade Sahade; Sitti Hajerah Hasyim (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect of social interaction on the learning motivation of Class X students of the Accounting Expertise Program at SMKN 1 Makassar. The variables in this study are social interaction as the independent variable (X) and learning motivation as the dependent variable (Y). Population study This amount 14 9 students class X Program Skill Accountancy State Vocational School 1 Makassar . The sampling technique uses the Proportioned Stratified Random Sampling technique , d with a sample of 60 students. Data collection techniques used are questionnaires and documentation. The data analysis technique used is descriptive percentage analysis, instrument test consisting of validity and reliability tests, test hypothesis consisting of simple linear regression analysis, product correlation analysis moment , coefficient of determination and t-test . Based on results of data analysis been done, then obtained models equality simple linear regression Y = 20.731 + 0.793 X, which means that for every additional unit of social interaction, motivation Study increased by 0.793 units. Results analysis person product moment correlation obtained a correlation coefficient of 0.686 which is included in the strong category. Next, from the results analysis coefficient determination (r 2 ) is obtained the value of r 2 = 0.470 means that the effect of social interaction on learning motivation is 47 percent and the remaining 53 percent is influenced by factor other. While the results of the t-test analysis were obtained mark significant 0.000 <0.05 which means social interaction has a significant effect on learning motivation, with thereby hypothesis accepted.